Management problems of high-rise buildings with reference to "Menara Promet" - Ahmad, Jaffar Derus; Mahmood, Abdul Azim; Abdul Rahman, Abdul Nasser; Shariff, Hanim Razak; Awi, Farida (1984)
This research was conducted as part of the partial requirements for a final semester project for students of the School of Business and Management. The purpose of this study was to investigate the management problems faced by managers of high-rise buildings, using “Menara Promet” as a case study. The dependent variable in this research is management problems, while the independent variables include location, building design, security, maintenance, and marketing of office space. Data were collected through both structured and unstructured interviews, as well as a 29-item questionnaire distributed to 200 respondents selected using the Stratified Random Sampling Method. The data were analyzed using frequency distribution, mean, standard deviation, variance, and cross-tabulation. The results indicated that management problems in high-rise buildings are influenced by the five independent variables, with building design identified as the most significant factor, followed by security. The findings highlight the need for improved design and security measures in high-rise building management to enhance overall operational efficiency.